The effects of zinc citrate, selenium citrate, and germanium citrate on hematological parameters of rabbits under heat stress - Marian Yuzviak; Yaroslav Lesyk; Ivan Luchka; Halyna Denys; Yuriy Salyha (Біологічні студії, 2024)
Background. The environmental crisis has affected the annual ambient temperature increase, adversely affecting the mammalian body. Due to their lack of sweat glands, Rabbits are more sensitive to heat stress than other animals. The effect of elevated ambient temperatures on the rabbit body leads to violations of blood parameters, endocrine regulation, immune and reproductive function, which reduces their productivity and increases animal mortality. Particular attention is now paid to the study of organic compounds of trace elements, which are characterized by high physiological activity, are non-toxic, have a wide range of biological effects, and have a positive impact on reducing the negative effect of elevated ambient temperatures on animals. However, their action depends on the element and its applied quantity. Therefore, the main objective of this study was to investigate the effect of zinc citrate, selenium citrate, and germanium citrate on changes in the number of blood cells in rabbits to mitigate the effects of heat stress. Materials and methods. The studies were conducted on young analog rabbits of the Termon White breed from 35 to 78 days of age. The rabbits were kept indoors at elevated ambient temperatures from 28.9 to 30 °C and relative humidity from 78.1 to 87.4 %. Animals of the control group were kept on the main diet with feeding of standard balanced granulated compound feed and water without restriction. Rabbits of groups I, II, and III of the study groups consumed the same compound feed as in control, but within 24 hours, they received water: group I – zinc citrate – 60 mg Zn/L or 12 mg Zn/kg of body weight; group II – selenium citrate – 300 μg Se/L or 60 μg Se/kg of body weight; group III – germanium citrate – 62.5 μg Ge/L or 12.5 μg Ge/kg of body weight. Using individual drinkers for each animal and placing the animals in different cages allowed us to control the amount of water consumed by each rabbit. Blood for the study was selected for supplementation on the 14th day of the preparatory period and the 14th and 29th days of the study period. During the study period, the room temperature was monitored, taking into account the temperature and humidity index. Results. The addition of micronutrient citrates to the diet of rabbits during 29 days of study under heat stress caused haematological changes in indicators compared to the control: the number of erythrocytes in the blood of rabbits of experimental groups I and II increased by 16.4 and 13.6 % and 19.9 and 14.5 % on day 14 and 29, respectively, in group III by 15.3 % on day 14; the haemoglobin content of groups I, II and III increased by 20.8, 21.6 and 19.5 % on day 14 and 11.1, 12.5 and 9.7 % on day 29; haematocrit value of groups I and II increased by 24.1 and 15.7 % and 21.1 and 16.5 % during the study, group III by 18.6% on day 14; the number of leukocytes of groups I, II and III decreased by 13.1 and 8.3 %; 11.2 and 10.4 % and by 11.4 and 9.3 % on days 14 and 29; the number of lymphocytes of groups I, II and III decreased by 25.9, 27.3 and 29.0 % on day 14 and by 20.4, 21.7 and 16.0 % on day 29; the number of monocytes of groups I and II increased by 14.8 and 21.3 % and 17.0 and 18.3 % over 29 days; the number of platelets in animals of group II decreased by 29.4 % on day 29, the average volume of red blood cells increased by 11.6 and 14.6 % on days 14 and 29 of the experiment. Conclusions. Adding micronutrient citrates to the rabbit diet mitigated the effects of heat stress on the body. The effect of these additives on animals resulted in significant changes in the hematological parameters of the rabbits’ blood, of which the best results were observed under the influence of selenium citrate (60 μg Se/kg body weight) and zinc citrate (12 mg Zn/kg body weight): red blood cell count (p <0.05–0.01), leukocyte (p <0.05–0.01), lymphocyte (p <0.05–0.01), monocyte (p <0.05–0.01), haemoglobin content (p <0.01–0.001), haematocrit value (p <0.01), compared to the control. Feeding germanium citrate led to less pronounced changes in these blood parameters.